Development, implementation and evaluation of nutrition module for trainers of persons with disabilities in community-based rehabilitation centres,Kelantan - Ting, Chen Seong (2014)
Persons with disabilities (PWD) are susceptible to malnutrition. However, little is known about the nutritional status and nutrition strategies among the local disability population. This study was conducted from June 2010 to July 2012. It aimed to assess the nutritional status of PWD, develop and evaluate the effectiveness of Nutrition Module for Trainers of Persons with Disabilities in community-based rehabilitation (CBR) centres, Kelantan. This study included three phases. At Phase I, nutrition assessment of PWD in CBR centres, Kelantan was conducted. A total of 467 PWD (281 children and adolescents; 186 adults) were recruited and their feeding and anthropometric data were collected using a structured questionnaire. The nutrition module and Nutrition Knowledge, Attitude and Practice Questionnaire about Persons with Disabilities (KAP-nOKU) were developed and validated in Phase 2. At Phase 3, an intervention study was conducted. Forty-five CBR teachers from Kelantan were recruited as the intervention group and 42 CBR teachers from Terengganu as the comparison group. The intervention group received the nutrition module training while the comparison group was trained on general health care issues about PWD. Baseline (TO) and follow up KAP-nOKU assessments at 1-month (Tl) and 6-month (T2) intervals after intervention were administered for both groups. Qualitative semi-structured interviews were conducted among 13 teachers from intervention group to explore the perceived motivations and barriers to their nutrition management for PWD at CBR centres. Results showed that there was a prevalence of 20.3% of PWD (17.8% children and adolescents; 24.2% adults) who were underweight while 22.8% (15.2% children and adolescents; 33.9% adults) were overweight or obese. At Phase 2, the validated KAP-nOKU contained 57 items with good-to-excellent internal consistencies for knowledge (KR20=0.63), attitude (a=0.67) and practice (a=0.82) domains. At Phase 3, repeated measures ANCOV A demonstrated that intervention group attained significantly higher nutrition knowledge (p<O.OOl) and practice (p=O.OOl) scores than comparison group at Tl (mean difference for knowledge= 6.95; mean difference for practice= 2.93) and T2 (mean difference for knowledge= 1 0.30; mean difference for practice= 4.78). Significant higher nutrition attitude (p=0.004) score for intervention group was observed at T2 (mean difference= 3.08). Teachers' positive personal attributes were identified as the primary motivation while PWD's resistance to teachers' positive nutrition management and lack of parental social support were the major barriers. In conclusion, this nutrition module is effective on improving the nutrition knowledge, attitude and practice of CBR teachers in Kelantan.